Information system sales and repair handphone services on pika cell - Al Amalul Khoir Amalul; Karnadi (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
Pika Cell is a counter that serves cellphone sales and services. In sales and service activities it is still not computerized or still written, where all the processes are from inputting data, and storing data in writing. The obstacles that occur are errors in managing the stock of cellphones and delays in handling cellphones that will be serviced. Therefore, the author provides a solution by creating a sales information system (e-commerce) and service delivery using the PHP programming language, MySQL database management system. This information system was developed using the Extreme Programming method, in that method there are still other stages, while the research itself uses a qualitative approach by coming directly to Pika Cell. The purpose of this final project is to create a sales information system (e-commerce) and mobile phone service where customers can order cell phones and get information on the estimated cost of cell phone damage online, so that the company's revenue can be achieved maximally and make it easier for customers to transact